2006
DOI: 10.5194/acp-6-4529-2006
|View full text |Cite
|
Sign up to set email alerts
|

Key aspects of stratospheric tracer modeling using assimilated winds

Abstract: Abstract. This study describes key aspects of global chemistry-transport models and their impact on stratospheric tracer transport. We concentrate on global models that use assimilated winds from numerical weather predictions, but the results also apply to tracer transport in general circulation models. We examined grid resolution, numerical diffusion, air parcel dispersion, the wind or mass flux update frequency, and time interpolation. The evaluation is performed with assimilated meteorology from the "operat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…The tendency for excessive equator to pole circulation intensity by the ECMWF analyses has been already diagnosed by analysis of satellite and soundings ozone data (de Laat et al, 2007), and with the calculation of stratospheric "age of air" (Bregman et al, 2006). The age of air is defined as the time that a stratospheric air mass has been out of contact with the troposphere.…”
Section: Consistency Test For the Large Scale Meridional Circulationmentioning
confidence: 99%
“…The tendency for excessive equator to pole circulation intensity by the ECMWF analyses has been already diagnosed by analysis of satellite and soundings ozone data (de Laat et al, 2007), and with the calculation of stratospheric "age of air" (Bregman et al, 2006). The age of air is defined as the time that a stratospheric air mass has been out of contact with the troposphere.…”
Section: Consistency Test For the Large Scale Meridional Circulationmentioning
confidence: 99%
“…[74] In previous studies it was shown that increasing the update frequency of the applied meteorology fields from 6 h to 3 h significantly improved the modeled stratospheric tracer fields [Legras et al, 2005;Berthet et al, 2006;Bregman et al, 2006]. Here we investigate the impact for the UT/LS for the integration period considered.…”
Section: Sensitivity To Different Horizontal Resolution and Meteorolomentioning
confidence: 99%
“…The stratospheric tracer distributions were improved significantly by including iterative advection [Bregman et al, 2006]. For a detailed description of the new model version TM5 the reader is referred to Krol et al [2005].…”
Section: Tm5mentioning
confidence: 99%
“…Consequently, it is possible to run simulations without reducing the time step. Although Bregman et al (2006) described the pitfalls of polar model grid averaging in global model studies of polar tracer transport in the stratosphere, numerical advection schemes that use a reduced grid generally perform well in model performance tests and are efficient solvers in various applications (Peterson et al, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…The influence of grid resolution on atmospheric composition simulation is a topic of continuous interest. Marchand et al (2003) and Bregman et al (2006) reported that grid resolution has a strong influence on the distribution of the tracer mixing ratio in the Polar Regions. In contrast, van den Broek et al (2003) reported a negligible improvement in methane transport model results with increasing horizontal grid resolution to 1 • × 1 • in a study on the effect of spatial resolution in the Polar Regions.…”
Section: Introductionmentioning
confidence: 99%